The Impact of Housing Vulnerability on the Relationship Between Social Capital, Residential Satisfaction, and Attitudes Toward Disadvantaged Groups in South Korea - Sungeun Kim; Seran Jeon (Buildings)
This study examines the relationships among social capital, residential satisfaction, and attitudes toward disadvantaged groups in South Korea, with a focus on the moderating effects of educational and employment vulnerability. Using data from the 2022 Seoul Survey, which included a sample of 39,340 individuals, the analysis employed Hayes’ Process Macro to assess both mediation and moderated mediation effects. The findings show that social capital significantly enhances residential satisfaction (β = 0.557, p < 0.001), which, in turn, positively influences attitudes toward disadvantaged groups (β = 0.411, p < 0.001). Notably, the impact of residential satisfaction on attitudes was stronger for individuals who were educationally and employment-vulnerable, underscoring the amplified role of housing conditions in shaping social attitudes for these groups. These results highlight the importance of strengthening social capital and implementing targeted housing policies to improve the well-being of vulnerable populations. Policy recommendations include integrating social capital-building initiatives with urban planning strategies and addressing the specific needs of vulnerable groups through tailored housing interventions to foster social cohesion and inclusivity. Future research should explore other dimensions of vulnerability and utilize longitudinal data to assess long-term impacts.